Simulation and experimental research on the parameter distribution of low-pressure Ar/O2 inductivly coupled plasma. (November 2017) - Chen, Junlin; Xu, Haojun; Wei, Xiaolong; Lv, HanYang; Song, Zhijie; Chen, Zenghui
Abstract: Adding electronegative gas to the inert gas is an important means of adjusting the plasma parameter distribution. In this paper, a fluid model of the Ar/O2 inductivly coupled plasma (ICP) is used to investigate the parameter distribution, while the electron energy distribution function (EEDF) and the transport coefficients are obtained by the Boltzmann equation solver module to improve the accuracy. The spatial-temporal evolution of the electron density and the electron temperature of the ICP are obtained and the influence of the discharge power and the oxygen mole ratio on the distribution of the ICP parameters is compared. Additionally, the physical mechanism is researched using the diffusion-transport theory of the plasma. In order to verify the reliability of the model results, an experiment is carried out to diagnose the discharge parameters. The results of the simulation and the experiment are performed for different power and oxygen mole ratios and a good qualitative and numerical agreement is obtained, indicating that the inclusion of the simulation results in a high accuracy. Highlights: A fluid model of the Ar/O2 ICP is used to investigate the parameter distribution, while the electron energy distribution function (EEDF) and the transport coefficients are obtained by the Boltzmann equation solver module to improve the accuracy. An experiment is carried out to diagnose the discharge parameters, and the results indicate that the fluid model with the Boltzmann equation module can well describe the parameters distribution of the Ar/O2 ICP.